The Causative Organisms of Bacterial Meningitis and their Antimicrobial Resistance Profiles in Iranian Children in 2011-2016 - Valian, Sepideh K.; Mahmoudi, Shima; Pourakbari, Babak; Banar, Maryam; Ashtiani, Mohammad T. H.; Mamishi, Setareh (Infectious Disorders - Drug Targets, 2020)
Objectives: The study aimed to describe the identity and antimicrobial resistance patterns of the causative agents of bacterial meningitis in children referred to Children’s Medical Center (CMC) Hospital, Tehran, Iran. Methods: This retrospective study was performed at CMC Hospital during a six-year period from 2011 to 2016. The microbiological information of the patients with a diagnosis of bacterial meningitis was collected and the following data were obtained: patients’ age, sex, hospital ward, the results of CSF and blood cultures, and antibiotic susceptibility profiles of isolated organisms. Results: A total of 118 patients with bacterial meningitis were admitted to CMC hospital. Sixty-two percent (n=73) of the patients were male. The median age of the patients was ten months (interquartile range [IQR]: 2 months-2 years) and the majority of them (n=92, 80%) were younger than two years of age. The highest number of patients (n=47, 40%) were admitted to the surgery department. Streptococcus epidermidis was the most frequent isolated bacterium (n=27/127, 21%), followed by Klebsiella pneumoniae (n=20/127, 16%), and Staphylococcus aureus (n=16/127, 12.5%). Blood culture was positive in 28% (n=33/118) of patients. Ampicillin-sulbactam and imipenem were the most effective antibiotics against Gram-negative bacteria isolated from CSF cultures. In the case of Gram-positive organisms, ampicillinsulbactam, vancomycin, and linezolid were the best choices. Imipenem was the most active drug against Gram-negative blood pathogens. Also, ampicillin and vancomycin had the best effect on Gram-positive bacteria isolated from blood cultures. Conclusion: Results of this study provide valuable information about the antibiotic resistance profiles of the etiologic agents of childhood meningitis, which can be used for prescription of more effective empirical therapies.
Keywords: causative organisms